Presentasi Poster P-01 s/d P-29 Hlm 251-308 - Jurnal Hemera Zoa (Hemera Zoa, 2016)
Presentasi Poster P-01 s/d P-29 Hlm 251-308 Prosiding KIVNAS Ke-14 PDHI 2016 di ICE, BSD City, Serpong, Tangerang Selatan.